Usefulness of HeberFERON® in patients with basal cell carcinoma - Natacha López Pupo; Yarien Manganelly Fonseca; María Elena Tablada Robinet; Ana Lucía Jacas Portuondo; Yaimaris Girón Maturell (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The basal cell carcinoma is the most frequent epithelial neoplasm, because it constitutes 60-80 % of all the cutaneous cancers.  Objective: To determine the answer to HeberFERON® in patients with basal cell carcinoma.  Methods:  An observational, descriptive and longitudinal study of 90 patients with basal cell carcinoma to whom HeberFERON® was administered was carried out at Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, from January, 2017 to December, 2019. Some demographic, clinical variables that responded to the treatment were analyzed.  Results: The average age was 63 years; there was a higher incidence of the male sex (58 for 64.4 %) and the cutaneous fototype II (56 for 62.0 %), with lesions located in the nose (42 for 46.7 %), as well as a prevalence of the nodular clinical subtype (41 for 45.6 %). The control of the disease was achieved in 100.0 % of the case material.  Conclusions: The HeberFERON® was very useful in patients with basal cell carcinoma, since in more than a half of them a complete response was obtained, with a minimum of adverse events, all of them light and moderate.